#neveragain - what midwives and midwifery scientists can learn from history - Nicola H. Bauer; Michaela Michel-Schuldt; Ulrike Geppert-Orthofer; Anja Katharina Peters; Daniela Erdmann; Cornelia Krapp; Wiebke Lisner (2024)
Hintergrund: Die Professionalisierung des Hebammenberufes und die Disziplinentwicklung der Hebammenwissenschaft befinden sich momentan in einem dynamischen Prozess. Dies beinhaltet auch zu einem großen Teil eine Reflexion des bisher Erreichten und noch Anzustrebenden. Insbesondere sollten die Entwicklungslinien sowie die damit einhergehenden Anpassungsleistungen an Werte und Normen in den Blick genommen werden. Eine Reflexion der Vergangenheit des Hebammenwesens findet beispielsweise im Rahmen von Identitäts- und Professionsbildung an den Hochschulen statt. Dort setzen sich die Studierenden unter anderem mit der „Reichshebammenführerin“ und ersten Präsidentin der International Midwives Union (IMU, heute ICM) Nanna Conti (1881-1951) auseinander. Ihr Name ist auf der Amtskette der Präsidentin des ICM eingraviert, die diese auch heute noch zu aktuellen Anlässen trägt. Dies wirft Kontroversen auf, die zeigen, dass eine Auseinandersetzung mit der Geschichte notwendig ist. Die politische Landschaft in Deutschland und weltweit verändert sich und rechte und rechtsextreme Parteien und andere Organisationen haben Zulauf und erstarken. Wahrzunehmen ist u.a. ein Roleback der Geschlechterbilder, der Frauen- und Familienbilder und der Umgang mit behinderten Menschen. Dies alles beeinflusst auch die Arbeit und die Haltung von Hebammen und erfordert eine kritische Reflexion. Geschehene Geschichte sollte nicht gelöscht werden, sondern ein verantwortungsvoller Umgang damit gefunden werden, um ggfs. auch Lehren daraus zu ziehen. Merkmale einer Profession sind nach Klemmt eine Tätigkeit mit Gemeinwohlorientierung, berufsständischen Normen in Form von Ethikkodizes sowie kollegiale Selbstkontrolle. Letzteres haben Hebammen im Rahmen eines internationalen Ethikkodex und einer Ethik für Hebammen des Deutschen Hebammenverbandes umgesetzt. Hieraus geht klar eine Unvereinbarkeit von rechter Ideologie und den Werten der Hebammen hervor. Ziel/Fragestellung: Der Workshop soll Hebammen (-wissenschaftler*innen) und Personen anderer Disziplinen aus Praxis, Lehre und Forschung für das Thema sensibilisieren und ermöglichen, gemeinsam in Kleingruppen an verschiedenen Aspekten dieses Themas zu arbeiten. Methodik: Angeboten wird ein offenes Veranstaltungsformat - ein Barcamp. Barcamps dienen dem inhaltlichen Austausch und der Diskussion, können aber auch bereits am Ende der Veranstaltung konkrete Ergebnisse vorweisen. Vor Ort findet zu Beginn eine Einführung in die Methode und die gemeinsame Programmplanung statt. Aufgrund der limitierten Zeit, werden bereits einige Eckpunkte festgelegt: Mittels eines Impulsvortrags zweier Expertinnen betrachten wir eingangs historische Entwicklungslinien. Die Teilnehmenden bringen sich anschließend in Kleingruppen zu bereits vorgegebenen Aspekten ein. Im großen Plenum wird aus den Kleingruppen berichtet. Alle Beiträge werden auf Flipcharts dokumentiert, was der Ergebnissicherung dient. Ergebnisse: Die Ergebnisse aus den einzelnen Kleingruppen können Hinweise auf zu bearbeitende Themen geben. Zudem können Impulse für die weitere Arbeit gesetzt werden. Relevanz: Die Ergebnisse sind für Berufspolitik, Hebammenwissenschaft, die Berufsgruppe der Hebammen, für die Praxis, Lehre und Forschung relevant. Empfehlungen/Schlussfolgerung: Die Auseinandersetzung mit diesem wichtigen Thema sollte auf verschiedenen Ebenen thematisiert und bearbeitet werden. Ethik und Interessenkonflikte: Es war nicht notwendig, die Forschungsarbeit einer Ethikkommission vorzulegen. Die Forschung wurde durch Eigenmittel finanziert. Es liegen keine Interessenkonflikte vor.

Midwifery in Germany on the path to professionalisation - Michaela Michel-Schuldt; Ruth Martis; Andrea Villmar (2024)
Background: According to Klemmt, professionalization has various characteristics based on the “feature theory approach” (merkmalstheoretischer Ansatz). Some of these features are already implemented or on their way to be implemented in a total of 29 European countries, according to an analysis on the state of professionalization of midwifery. For example, in most countries, progress in professionalizing midwifery had been made by moving education of midwives into higher education, combined with opportunities for postgraduate study and research. Features that fall within the realm of midwifery regulation are currently less of a focus of the professionalization debate. Specifically, these are professional and thematic autonomy in the practice of the profession, exclusive authorization/licensing in the practice of the profession, mandatory professional norms in the form of codes of ethics, as well as collegial self-regulation and the formation and establishment of an autonomous regulatory body. The latter point will be the focus of this paper. Aim/question: Which possibilities and forms of establishing autonomous regulatory bodies in midwifery exist internationally? Can best practice examples be found among them and how can these be transferred to Germany? Methodology: Within the framework of a policy analysis by means of document analysis, the international context of professional self-regulation was first considered based on the global standard for the regulation of the midwifery profession of the International Confederation of Midwives (ICM). Autonomous regulatory bodies (professional chambers, councils, boards) of different countries were measured against the ICM standard and best practice examples were examined for their transferability to the German (health) policy system. Results: The Midwifery Council in New Zealand, as an autonomous regulatory body, implements all points of the ICM standard. The type and scope of midwifery practice (e.g. professional regulations) are defined by the Council, as are the competencies and regulations for education and training; the Midwifery Council organizes the obligatory registration/licensing and is responsible for compliance with re-licensing and thus the maintenance and expansion of competence. It regulates continuing professional education and has established a complaints system that can also impose sanctions. A binding code of conduct/professional ethics exists. The aim of the regulation is to protect the service users, which is why they are represented on the board of the Midwifery Council. A transfer to the German system is largely possible and could serve to strengthen the professionalization of midwifery. Relevance: Midwives in Germany are on the path to professionalization. In addition to the academization that has already taken place, the focus can now be placed on the area of self-regulation and -governance. Recommendations/conclusion: The establishment of an autonomous regulatory body to strengthen regulation and self-governance based on international standards is the next necessary step on the way to professionalization of midwifery in Germany. Ethics and conflicts of interest: A vote on ethics was not necessary. The research was financed by own resources. There are no conflicts of interest.

Opportunities and limitations of the “gold standard” Cochrane Review in evidence-based midwifery care - Michaela Michel-Schuldt; Evelyn Lesta; Marina Weckend; Ruth Martis; Beate Ramsayer; Hanna Gehling (2024)
Background: The Cochrane Database of Systematic Reviews is one of the largest and best-known collections of reviews of scientific evidence in health care. It is based on the results of studies that meet certain quality criteria and includes mainly randomized controlled trials (RCTs). These are considered the “gold standard” for assessing the effectiveness of an intervention or treatment and are ranked at the top of the evidence pyramid. In German-speaking countries, midwives and scientists use the Cochrane Library reviews as sources of high quality scientific evidence, and their dissemination is supported by the German Society for Midwifery Science (DGHWi). For example, the International Midwifery Science Section of the DGHWi has been collaborating with Cochrane Germany for several years: Section members regularly search current reviews for relevance to midwives and translate scientific abstracts. Cochrane Methods responded to criticism of the methodological approach in the past with transparency and continuous methodological development. The question of clinical relevance and significance for the target population can also be a basic problem in some studies. Particularly in the field of midwifery science, RCTs have long been critically debated because they cannot adequately investigate many relevant questions. Aim/objective: Due to the high importance of Cochrane Reviews, we want to ask the question: what are the possibilities and limitations of systematic reviews in midwifery science? In this context, we want to discuss, among other things, to what extent a hierarchization of evidence is useful. Methodology: A short keynote presentation will provide insight into the methodology and evaluation of these reviews. This will serve as the basis for the subsequent moderated discussion session, to which we invite experts to address the topic. Results: The oral contributions of participants will be recorded by members of the International Section and will be published in the Journal of Midwifery Science to stimulate a broader debate. Relevance: Evidence-based midwifery care relies on critical review of scientific evidence, its generation and evaluation. Recommendations/conclusion: Cochrane reviews make an essential contribution to the generation and provision of evidence for midwifery care. Consideration should be given to the possibilities and limitations of this methodology. The classification of an evidence hierarchy based on study types should be questioned. Ethics and conflicts of interest: A vote on ethics was not necessary. The research was financed by own resources. There are no conflicts of interest.

Geburtshilfliche Versorgung von Frauen ohne Krankenversicherung in Deutschland - Michaela Michel-Schuldt; Heusermann Gila (Public Health Forum, 2021)
Zusammenfassung In Deutschland leben schätzungsweise 60,000 Menschen ohne Krankenversicherung, darunter auch Frauen im reproduktiven Alter. Diese schwangeren Frauen, Gebärende und deren Kinder sind einem erhöhten gesundheitlichen Risiko ausgesetzt. Um deren Versorgung sicherzustellen, bieten Hebammen und Gynäkolog*innen als Teil eines interdisziplinären Teams ehrenamtlich und unentgeltlich Dienste an. Auch wenn solche regionalen Lösungen existieren, müssen bundesweite Regelungen entwickelt und umgesetzt werden.

Midwife-Led Care in Low- and Middle-Income Countries with a Focus on Implementation in Bangladesh - Michaela Michel-Schuldt (2021)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱: Rigorous research on midwife-led models of care in high-income countries show that they are effective and should be offered to most women, as they provide benefits for childbearing women and their newborns. There are few studies on midwife-led models of care in low- and middle-income countries (LMIC). A better understanding of midwife-led care (MLC) in LMICs is needed. 𝗔𝗶𝗺: The overall aim was to explore how MLC is being implemented in LMICs. The three objectives were to systematically review the current evidence on midwife-led care in low- and middle-income countries, to assess the policies and health system efforts related to midwife-led care in a LMIC (Phase 1) and then to explore how midwife-led care was implemented in this country (Phase 2). 𝗠𝗲𝘁𝗵𝗼𝗱: First, two reviews were conducted. In Phase 1, a policy and health systems analysis in Bangladesh, was undertaken. Finally, Phase 2 was a case study in Bangladesh using an explanatory mixed methods design. In this primary study, a multistage purposeful sampling technique was used and face to face interviews and focus groups were conducted. Data analysis used a framework approach. A synthesis of all phases identified the essential elements of MLC in these contexts. 𝗙𝗶𝗻𝗱𝗶𝗻𝗴𝘀: The reviews showed that midwife-led care may be cost-effective, is likely to improve maternal mortality and morbidity, reduce interventions and improves quality of care, although more research is needed. MLC is provided in a variety of settings: urban and rural; in primary, secondary or tertiary facilities; in the private and public sector; in free-standing or alongside midwife-led units; and midwives work alone or in teams. Workforce shortages exist and negatively impact on the provision of MLC. Standards of education, regulation and training influence the quality of care and supportive environments are important. The policy and health systems analysis highlighted the need for leadership and resource mobilisation. The case study identified four themes in relation to the implementation of MLC in Bangladesh. These were addressing the heart and soul of MLC, empowering midwives to become leaders, structuring midwife-led care and providing care across the continuum. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: Midwife-led care in low- and middle-income countries has potential to improve outcomes in maternal and newborn health and might be cost-effective. The implementation of midwife-led care varies and supportive systems and workforce planning are key to its success. The essential elements of MLC that were identified could be applied to similar contexts.

Editorial: Women's Health in Low-Resourced Countries: Epidemiology, Governance, - Ulrich Laaser; Vesna Bjegovic-Mikanovic; Motasem Hamdan; Flavia Senkubuge; Michaela Michel-Schuldt (2020)

The provision of midwife-led care in low-and middle-income countries: An - Michaela Michel-Schuldt; Alison McFadden; Mary Renfrew; Caroline Homer (Midwifery, 2020)
BACKGROUND: The provision of midwife-led care, the model of care in which midwives are the lead professionals for women and newborn infants across the continuum, has been shown to be effective in improving outcomes for women and newborn infants, but predominantly based on research in high-income countries. OBJECTIVE: To explore how midwife-led care is provided in low- and middle-income countries. The specific question was to examine how, where and by whom has midwife-led care been provided in low-and-middle-income countries? DESIGN: An integrative literature review was undertaken and included studies using a range of methods. DATA SOURCES: A systematic search was conducted in Pubmed, EMBASE (Ovid), Web of Science, Scopus, Google Scholar, The Cochrane Library and hand-searching of relevant journals and website of International Organizations and relevant grey-literature. REVIEW METHODS: After applying inclusion criteria, systematic sifting and quality assessment processes, data were extracted from relevant studies. The software program NVivo was used to initially extract the findings and results of the studies. Coded data from primary data sources were iteratively compared, using patterns and themes as per the conceptual framework of the WHO on skilled health personnel providing care for childbearing women and newborn infants, including an analysis of the competent provider, standards of practice and the enabling environment. FINDINGS: Of a total of 3324 articles retrieved, 31 studies were included. There were 18 qualitative, nine quantitative and four mixed method studies with different levels of quality from five of six global regions published between 1997 and 2017. In these studies, midwife-led care was not found to be a standardised model in low- and middle-income countries (LMIC) and there was limited evidence on the effectiveness of midwife-led care in these countries. Care provided across the continuum was however described in most studies. Standards of practice in education, regulation and training varied widely as did the enabling environment in which midwife-led care took place. CONCLUSION AND IMPLICATION FOR PRACTICE AND RESEARCH: Midwife-led care is provided across low- and middle-income countries but lack of enabling factors limits the quality of care that midwives can provide. Further research about this model of care is needed to understand the ingredients of successful implementation, their effectiveness and sustainability.

Asking Different Questions: A Call to Action for Research to Improve the Quality - Holly P Kennedy; Melissa Cheyney; Hannah G Dahlen; Soo Downe; Maralyn J Foureur; Caroline S E Homer; Elaine Jefford; Alison McFadden; Michaela Michel-Schuldt; Jane Sandall; Hora Soltani; Anna M Speciale; et al. (Journal of midwifery & women's health, 2018)

Asking different questions: A call to action for research to improve the quality - Holly P Kennedy; Melissa Cheyney; Hannah G Dahlen; Soo Downe; Maralyn J Foureur; Caroline S E Homer; Elaine Jefford; Alison McFadden; Michaela Michel-Schuldt; Jane Sandall; Hora Soltani; Anna M Speciale; et al. (Midwifery, 2018)

Asking different questions: A call to action for research to improve the quality - Holly P Kennedy; Melissa Cheyney; Hannah G Dahlen; Soo Downe; Maralyn J Foureur; Caroline S E Homer; Elaine Jefford; Alison McFadden; Michaela Michel-Schuldt; Jane Sandall; Hora Soltani; Anna M Speciale; et al. (Birth (Berkeley, Calif.), 2018)
Despite decades of considerable economic investment in improving the health of families and newborns world-wide, aspirations for maternal and newborn health have yet to be attained in many regions. The global turn toward recognizing the importance of positive experiences of pregnancy, intrapartum and postnatal care, and care in the first weeks of life, while continuing to work to minimize adverse outcomes, signals a critical change in the maternal and newborn health care conversation and research prioritization. This paper presents "different research questions" drawing on evidence presented in the 2014 Lancet Series on Midwifery and a research prioritization study conducted with the World Health Organization. The results indicated that future research investment in maternal and newborn health should be on "right care," which is quality care that is tailored to individuals, weighs benefits and harms, is person-centered, works across the whole continuum of care, advances equity, and is informed by evidence, including cost-effectiveness. Three inter-related research themes were identified: examination and implementation of models of care that enhance both well-being and safety; investigating and optimizing physiological, psychological, and social processes in pregnancy, childbirth, and the postnatal period; and development and validation of outcome measures that capture short and longer term well-being. New, transformative research approaches should account for the underlying social and political-economic mechanisms that enhance or constrain the well-being of women, newborns, families, and societies. Investment in research capacity and capability building across all settings is critical, but especially in those countries that bear the greatest burden of poor outcomes. We believe this call to action for investment in the three research priorities identified in this paper has the potential to achieve these benefits and to realize the ambitions of Sustainable Development Goal Three of good health and well-being for all.

Barriers to and strategies for addressing the availability, accessibility, - Caroline S E Homer; Sofia Castro Lopes; Andrea Nove; Michaela Michel-Schuldt; Frances McConville; Nester T Moyo; Martha Bokosi; Petra Ten Hoope-Bender (BMC pregnancy and childbirth, 2018)
BACKGROUND: In a post-2015 development agenda, achieving Universal Health Coverage (UHC) for women and newborns will require a fit-for-purpose and fit-to-practice sexual, reproductive, maternal, adolescent and newborn health (SRMNAH) workforce. The aim of this paper is to explore barriers, challenges and solutions to the availability, accessibility, acceptability and quality (AAAQ) of SRMNAH services and workforce. METHODS: The State of the World's Midwifery report 2014 used a broad definition of midwifery ("the health services and health workforce needed to support and care for women and newborns") and provided information about a wide range of SRMNAH workers, including doctors, midwives, nurses and auxiliaries. As part of the data collection, 36 out of the 73 participating low- and middle-income countries conducted a one-day workshop, involving a range of different stakeholders. Participants were asked to discuss barriers to the AAAQ of SRMNAH workers, and to suggest strategies for overcoming the identified barriers. The workshop was facilitated using a discussion guide, and a rapporteur took detailed notes. A content analysis was undertaken using N-Vivo software and the AAAQ model as a framework. RESULTS: Across the 36 countries, about 800 participants attended a workshop. The identified barriers to AAAQ of SRMNAH workers included: insufficient size of the workforce and inequity in its distribution, lack of transportation, user fees and out of pocket payments. In some countries, respondents felt that women mistrusted the workforce, and particularly midwives, due to cultural differences, or disrespectful behaviour towards service users. Quality of care was undermined by a lack of supplies/equipment and inadequate regulation. Against these, countries identified a set of solutions including adequate workforce planning supported by a fast and equitable deployment system, aligned with the principles of UHC. Acceptability and quality could be improved with the provision of respectful care as well as strategies to improve education and regulation. CONCLUSIONS: The number and scale of the barriers still needing to be addressed in these 36 countries was significant. Adequate planning and policies to support the development of the SRMNAH workforce and its equitable distribution are a priority. Enabling strategies need to be put in place to improve the status and recognition of midwives, whose role is often undervalued.

Continuous professional development of Liberia's midwifery workforce-A - Michaela Michel-Schuldt; Matilda Billy Dayon; Robin Toft Klar; Marion Subah; Esther King-Lincoln; Cecelia Kpangbala-Flomo; Raphaël Broniatowski (Midwifery, 2018)
BACKGROUND: Maternal and newborn mortality remains high in Liberia. There is a severe rural-urban gap in accessibility to health care services. A competent midwifery workforce is able to meet the needs of mothers and newborns. Evidence shows that competence can be assured through initial education along with continuous professional development (CPD). In the past, CPD was not regulated and coordinated in Liberia which is cpommon in the African region. AIM: To Support a competent regulated midwifery workforce through continuous professional development. METHODOLOGY: A new CPD model was developed by the Liberian Board for Nursing and Midwifery. With its establishment, all midwives and nurses are required to undertake CPD programmes consisting of certified training and mentoring in order to renew their practicing license. The new model is being piloted in one county in which regular mentoring visits that include skills training are being conducted combined with the use of mobile learning applications addressing maternity health issues. Quality control of the CPD pilot is assured by the Liberian Board for Nursing and Midwifery. The mentoring visits are conducted on a clinical level but are coordinated on the national and county level. SUCCESSES AND SUSTAINABILITY: CPD using mobile learning on smartphones and regular mentoring visits not only improved knowledge and skills of midwives and nurses but also provided a solution to enhance accessibility in rural areas through improved communication and transportation, as well as improved career development of health personnel working in remote areas. Mentors were trained on a national, county, and health facility level in the pilot county with mentoring visits conducted regularly. CONCLUSION: The CPD programme of the Liberian Board for Nursing and Midwifery, currently in pilot-testing by various partners, aims to highlight the positive impact of the coordinating role of both the regulatory body and health authorities. Using regular process and programme reviews to improve capacity, knowledge, and skills of health professionals.

Erhebung zur Hebammenversorgung in der Stadt Mainz und dem Landkreis Mainz-Bingen - Analyse der Arbeitsbelastung von freiberuflichen Hebammen und ausgewählten Variablen - Heusermann Gila; Beringhoff Annika; Greening Monika; Michaela Michel-Schuldt (German Medical Science GMS Publishing House, 2018)
Hintergrund: In Deutschland soll jeder Schwangeren, Gebärenden und Wöchnerin die Hilfe einer Hebamme zugänglich gemacht werden. Dieser Versorgungsanspruch ist flächendeckend - wegen des Hebammenmangels - nicht mehr möglich. Verlässliche Zahlen gibt es bisher jedoch kaum. Ziel: Um die Datenlage hinsichtlich der Anzahl und des Leistungsumfangs der Hebammen in der Stadt Mainz und dem Landkreis Mainz-Bingen zu ermitteln, wurde eine Erhebung zur Hebammenversorgung durchgeführt. Die Ergebnisse wurden in weiteren Teilarbeiten genauer analysiert und durch eine qualitative Forschungsarbeit zur Arbeitsbelastung ergänzt. Methodik: Basierend auf der Studie des Hebammenlandesverbandes Baden-Württemberg/Universität Freiburg wurden freiberufliche und angestellte Hebammen in Mainz und Landkreis Mainz-Bingen in einem Survey nach Leistungsspektrum und Umfang ihrer Hebammentätigkeit im Zeitraum vom 22.03.-18.04.2017 befragt. Die Ergebnisse wurden deskriptiv ausgewertet. In den weiteren Teilarbeiten wurden ausgesuchte Variablen uni- und bivariat analysiert und der Aspekt der Arbeitsbelastung durch eine Gruppendiskussion bearbeitet. Ergebnis: Die deskriptive Datenanalyse ergab, dass freiberuflich tätige Hebammen in Mainz und im Landkreis Mainz-Bingen im gesamten Betreuungsbogen arbeiten. Die angestellten Hebammen sind vor allem im Kreißsaal tätig. Während die Anzahl der Wochenarbeitsstunden in beiden Bereichen etwa gleich sind, gaben die angestellten Hebammen einen höheren Verdienst an. Als Belastung wurden hohes Arbeitsaufkommen und Zeitmangel bei der Betreuung genannt. Im Gegensatz zu der mangelhaften Zufriedenheit mit dem Einkommen ist die Zufriedenheit mit dem Beruf sehr hoch. Unabhängig von der Art der Berufsausübung ist eine Reduktion der Arbeitszeit beziehungsweise Aufgabe der Hebammentätigkeit die Folge. Die uni- und bivariate Analyse ergab, dass ein signifikanter Zusammenhang zwischen dem Alter der Hebammen und der Zufriedenheit mit dem Einkommen nachgewiesen werden konnte. Zudem wurde eine Zunahme der Anzahl freiberuflicher Hebammen und eine Abnahme der Anzahl angestellter Hebammen herausgestellt. Kein signifikanter Zusammenhang war erkennbar zwischen dem Alter der Hebammen und der Zufriedenheit mit dem Beruf und zwischen der Zufriedenheit mit der Arbeitszeit und der Art der Berufsausübung. Im qualitativen Teil, wurde herausgearbeitet, dass sich Hebammen durch soziokulturelle Faktoren, wirtschaftliche Faktoren und professionelle Faktoren belastet fühlen. Um die Arbeitsbelastungen zu reduzieren, vollzogen sie Veränderungen in ihrem Arbeitsleben. Außerdem wurden Lösungsansätze und Akteure benannt, die für eine zukünftige Entlastung sorgen könnten. Relevanz: Die Datenlage in Deutschland wurde durch die Erhebungen verbessert. Empfehlungen: Es sind weitere Untersuchungen notwendig, um repräsentativere Ergebnisse liefern zu können. Um verlässliche Zahlen darstellen zu können, wäre eine verpflichtende Registrierung in einer Kammer nötig. Weiterführende Fragen aus der Erhebung sind, wie auf Stadt bzw. Kreisebene die Arbeitssituation verbessert werden kann und was auf Landes- bzw. Bundesebene getan werden muss. Des Weiteren, wie Akteure zusammengeführt werden können, um genaue Lösungskonzepte zu erarbeiten und an den richtigen Stellen zu etablieren. Ethik und Interessenkonflikt: Die Forschungsarbeit wurde aus folgendem Grund keiner Ethikkommission vorgelegt: Forschungsethische Grundsätze wurden eingehalten und die Klientel als nicht vulnerabel eingestuft. Sie wurde durch Eigenmittel finanziert. Es liegt kein Interessenkonflikt vor. Das PDF des für die Tagung eingereichten Posters ist in deutscher Sprache als Anhang 1 [Anh. 1] verfügbar.

The development of a global Midwifery Education Accreditation Programme - Andrea Nove; Sally Pairman; Leah F Bohle; Shantanu Garg; Nester T Moyo; Michaela Michel-Schuldt; Axel Hoffmann; Gonçalo Castro (Global health action, 2018)
BACKGROUND: Many countries are responding to the global shortage of midwives by increasing the student intake to their midwifery schools. At the same time, attention must be paid to the quality of education being provided, so that quality of midwifery care can be assured. Methods of assuring quality of education include accreditation schemes, but capacity to implement such schemes is weak in many countries. OBJECTIVE: This paper describes the process of developing and pilot testing the International Confederation of Midwives' Midwifery Education Accreditation Programme (ICM MEAP), based on global standards for midwifery education, and discusses the potential contribution it can make to building capacity and improving quality of care for mothers and their newborns. METHODS: A review of relevant global, regional and national standards and tools informed the development of a set of assessment criteria (which was validated during an international consultation exercise) and a process for applying these criteria to midwifery schools. The process was pilot tested in two countries: Comoros and Trinidad and Tobago. RESULTS: The assessment criteria and accreditation process were found to be appropriate in both country contexts, but both were refined after the pilot to make them more user-friendly. CONCLUSION: The ICM MEAP has the potential to contribute to improving health outcomes for women and newborns by building institutional capacity for the provision of high-quality midwifery education and thus improved quality of midwifery care, via improved accountability for the quality of midwifery education.

Current and future availability of and need for human resources for sexual, - Maria Guerra Arias; Andrea Nove; Michaela Michel-Schuldt; Luc de Bernis (International journal for equity in health, 2017)
BACKGROUND: The WHO African region, covering the majority of Sub-Saharan Africa, faces the highest rates of maternal and neonatal mortality in the world. This study uses data from the State of the World's Midwifery 2014 survey to cast a spotlight on the WHO African region, highlight the specific characteristics of its sexual, reproductive, maternal and newborn health (SRMNH) workforce and describe and compare countries' different trajectories in terms of meeting the population need for services. METHODS: Using data from 41 African countries, this study used a mathematical model to estimate potential met need for SRMNH services, defined as "the percentage of a universal SRMNH package that could potentially be obtained by women and newborns given the composition, competencies and available working time of the SRMNH workforce." The model defined the 46 key interventions included in this universal SRMNH package and allocated them to the available health worker time and skill set in each country to estimate the potential met need. RESULTS: Based on the current and projected potential met need in the future, the countries were grouped into three categories: (1) 'making or maintaining progress' (expected to meet more, or the same level, of the need in the future than currently): 14 countries including Ghana, Senegal and South Africa, (2) 'at risk' (currently performing relatively well but expected to deteriorate due to the health workforce not keeping pace with population growth): 6 countries including Gabon, Rwanda and Zambia, and (3) 'low performing' (not performing well and not expected to improve): 21 countries including Burkina Faso, Eritrea and Sierra Leone. CONCLUSION: The three groups face different challenges, and policy solutions to increasing met need should be tailored to the specific context of the country. National health workforce accounts should be strengthened so that workforce planning can be evidence-informed.

Asking different questions: research priorities to improve the quality of care - Holly Powell Kennedy; Sashiyo Yoshida; Anthony Costello; Eugene Declercq; Marcos A Dias; Elizabeth Duff; Atf Gherissi; Karyn Kaufman; Frances McConville; Alison McFadden; Michaela Michel-Schuldt; Nester T Moyo; et al. (The Lancet. Global health, 2016)